(untitled) (Innovaciones Educativas, 2012)
This case study reflects upon the experience of implementing a plan for a student with attention-deficit hyperactivity disorder attending a high school within an EFL environment in Costa Rica. The plan consisted of a set of four observations and four work sessions. In addition, the study reports on the strategies and techniques used with the student and the teacher in order to improve the student’s performance in the class. The results and the analysis of the case study are also discussed. One of the main findings is that this disorder can be effectively treated.